Assessment of Financial Growth and Shareholder Value in India's Robotics and Automation Industry (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research investigates the correlation between shareholder value and retained earnings in prominent Indian automation and robotics companies, such as Tata Elxsi, Maruti Suzuki, and Tata Motors, from 2015 to 2023. In order to assess the influence of retained earnings on shareholder wealth in this dynamic sector, the investigation implements a longitudinal study design. This study employs a regression model that incorporates financial metrics, including the price-to-earnings (P/E) ratio, retained earnings (RE), market share price, net profit margin (NPM), return on equity (ROE), earnings per share (EPS), return on capital employed (ROCE), and return on assets (ROA). These indicators clarify the relationship between shareholder wealth and retained earnings. The study also highlights the financial strategies used by these organizations to improve profitability retention in India's rapidly expanding automation and robotics sectors. The findings offer valuable insights for industry specialists, investors, and policymakers who are interested in comprehending the complexities of the sector.